The Biopolitics in Subjective Regulation by Maternal Discourse: The Effects of Governing the Female Protagonists Body in the Miniseries Maid (Global Journal of Human-Social Science, 2023)
In this research, we aim to describe and discursively analyze the utterances of the main character of the miniseries Maid (MAID, 2021), regarding subjective regulation by maternal discourse. We rely on the perspective of French Discourse Analysis, on Foucauldian studies on biopolitics in the regulation of life and the behaviors that legitimize the character as a mother, wife, daughter and family member. The anatomo-political practices of the body by the biopowers with individual homogenizing effects and the biopolitics that permeates the populations will endorse the subjective regulation of the protagonist, splitting Alex by the psychological violence represented by the institutions family and State. The protagonist Alex suffered psychological, financial, labor and gender abuse as a single mother. We question how biopower and biopolitics operate subjectivation techniques through wills of truth to normalize the institution of the traditional and conservative family, whose tonic is patriarchal.
Keywords: biopolitics; government of the body; subjectivity; violence